My journey after a mild infection with COVID-19: I want my old brain back - Clarissa Lin Yasuda (Arquivos de Neuro-Psiquiatria)
ABSTRACT Although neurocognitive dysfunction has been observed after infection by SARS-CoV-2, few studies have detailed these alterations or demonstrated their impact on daily life activities and work. Here, I describe the sequence of events following a mild COVID-19 infection in August 2020 (which now is described as “post-COVID syndrome”) and comment on my ensuing limitations associated with cognitive difficulties, headache, fatigue and sleepiness. Furthermore, I discuss the efforts that I have made to recover from my infection since its beginning and the strategies adopted for living with persistent restrictions in terms of cognitive performance.